2021
DOI: 10.1111/1471-0528.16774
|View full text |Cite
|
Sign up to set email alerts
|

Trichomoniasis and adverse birth outcomes: a systematic review and meta‐analysis

Abstract: Background Trichomoniasis commonly affects women of childbearing age and has been linked to several adverse birth outcomes.Objective To elucidate the association between trichomoniasis in pregnant women and adverse birth outcomes, including preterm delivery, prelabour rupture of membranes and low birthweight.Search strategy MEDLINE, EMBASE and ClinicalTrials.gov were systematically searched in December 2020 without time or language restrictions.Selection criteria Original research studies were included if they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
45
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 61 publications
(301 reference statements)
1
45
2
1
Order By: Relevance
“…A 2014 meta-analysis found that TV infection was associated with an increased risk of PTB (RR, 1.34; 95% CI, 1.19–1.51; P < 0.001) 7 in 6 studies of more than 20,000 participants and controlling for STI coinfection. More recently, a 2021 meta-analysis found a similar magnitude of the effect of TV on PTB (OR, 1.27; 95% CI, 1.08–1.50), analyzing 11 studies including >80,000 participants 6 . Our study may have been underpowered to detect an effect, given a potentially small effect size, as suggested by the meta-analyses.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…A 2014 meta-analysis found that TV infection was associated with an increased risk of PTB (RR, 1.34; 95% CI, 1.19–1.51; P < 0.001) 7 in 6 studies of more than 20,000 participants and controlling for STI coinfection. More recently, a 2021 meta-analysis found a similar magnitude of the effect of TV on PTB (OR, 1.27; 95% CI, 1.08–1.50), analyzing 11 studies including >80,000 participants 6 . Our study may have been underpowered to detect an effect, given a potentially small effect size, as suggested by the meta-analyses.…”
Section: Discussionmentioning
confidence: 60%
“…More recently, a 2021 meta-analysis found a similar magnitude of the effect of TV on PTB (OR, 1.27; 95% CI, 1.08-1.50), analyzing 11 studies including >80,000 participants. 6 Our study may have been underpowered to detect an effect, given a potentially small effect size, as suggested by the meta-analyses. Lack of association between TV and PTB was seen in 3 recent studies in underserved populations: adolescents in Illinois 21 (adjusted prevalence ratio, 1.19; 95% CI, 0.58-2.43), South African women with 37% HIV seroprevalence 22 (aOR, 1.1; 95% CI, 0.7-1.9), and Australian indigenous women 23 (aOR, 0.66; 95% CI, 0.39-1.12).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations